THE INFLUENCE OF LEARNING MOTIVATION ON STUDENT LEARNING OUTCOMES: ANALYSIS OF INTERNAL AND EXTERNAL FACTORS FOR SMA NEGERI 6 PALANGKA RAYA CITY STUDENTS - Mega Kurniawati; Ni Putu Diah Agustin Permanasuri; Lola Cassiophea; Indah Gumilang Dwinanda; Renna Jesisca Sihombing (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2025)
This research analyzes the influence of learning motivation on student learning outcomes at SMA Negeri 6 Palangka Raya City. Quantitative methods with descriptive and correlational designs were used, involving 100 students who filled out questionnaires regarding motivation and learning outcomes in Mathematics. The research results showed that the average student learning motivation reached 85.75%, while learning outcomes were only 78.30%. Even though there is a positive relationship between motivation and learning outcomes (r = 0.15), the t-test results (p = 0.128) show there is no significant effect. External factors such as innovative teaching methods and the home learning environment are proven to influence learning outcomes more. In conclusion, although motivation is important, other factors also play a significant role in improving student learning outcomes